Analisis Tingkat Kesehatan Kinerja Keuangan Perusahaan BUMN Bidang Industri Pertahanan (Indhan) Indonesia Periode 2015-2019 - Angga Nugraha; Tjetjep Djuwarsa; Ine Mayasari (Indonesian Journal of Economics and Management, 2020)
This study seeks to describe the quality of financial performance of Indonesian Defense Industry (Indhan) BUMN companies in the 2015-2019 period as measured using a reference standard based on the Decree of the Minister of State-Owned Enterprises (BUMN) Number (KEP-100/MBU/2002). The assessment indicators used as an assessment tool consist of 8 indicators, namely Return on Equity, Return on Investment, cash ratio, current ratio, collection periods, inventory turnover, total asset turnover, and the ratio of total equity to total assets. The results of the study showed varied results. PT Dahana (Persero) obtained a “Sehat AA” level of financial health in 2015-2018 and “Sehat A” in 2019. PT Industri Telekomunikasi Indonesia (Persero) obtained a “Kurang Sehat B” level of financial health in 2015-2016, then in 2017 received a "Kurang Sehat BB" to decrease in 2018 and 2019 to "Tidak Sehat CCC". PT Pindad (Persero) obtained financial performance results with a value of "Kurang Sehat BBB" in 2015-2017, then "Sehat A" in 2018 and decreased in 2019 to "Kurang Sehat BBB”.